Communication Technologies in Prepaid Smart Meters: A Systematic Review - Sharma, Ankit; Birla, Dinesh; Lalwani, Mahendra (Asian Journal of Electrical Sciences, 2016)
In today’s world, electromechanical or digital energy meters are used for energy metering and billing. It consumes considerable time and labour. Tradition billing system was slow, costly and lacked in flexibility as well as reliability. Today, accuracy in electrical billing is highly desired. The smart energy meter gives real time consumption as well as accurate billing. Wireless Energy Meter is able to send its data via wireless communication to personal computers or a remote device where monitoring and analysis of the data can be easily made. In smart metering, different techniques in communication system like WIMAX, Zig-Bee and GSM etc are more popular. This paper presents a brief review of the work carried out by the various researchers in the field of Advanced Metering Infrastructure (AMI) techniques and also the various communication systems being used in smart metering technology. They are differentiated by various factors involved in daily energy requirements. They are also compared among one another and it is shown by various parameters to demonstrate this comparison.